Mendelian Disorders in an Interstitial Cystitis/Bladder Pain Syndrome Cohort. Issue 1 (27th November 2022) - Estrella, Elicia; Rockowitz, Shira; Thorne, Marielle; Smith, Pressley; Petit, Jeanette; Zehnder, Veronica; Yu, Richard N.; Bauer, Stuart; Berde, Charles; Agrawal, Pankaj B.; Beggs, Alan H.; Gharavi, Ali G.; et al.
Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic pain disorder causing symptoms of urinary frequency, urgency, and bladder discomfort or pain. Although this condition affects a large population, little is known about its etiology. Genetic analyses of whole exome sequencing are performed on 109 individuals with IC/BPS. One family has a previously reported  SIX5  variant (ENST00000317578.6:c.472G>A, p.Ala158Thr), consistent with Branchiootorenal syndrome 2 (BOR2). A likely pathogenic heterozygous variant in  ATP2A2  (ENST00000539276.2:c.235G>A, p.Glu79Lys) is identified in two unrelated probands, indicating possible Darier‐White disease. Two private heterozygous variants are identified in  ATP2C1  (ENST00000393221.4:c.2358A>T, p.Glu786Asp (VUS/Likely Pathogenic) and ENST00000393221.4:c.989C>G, p.Thr330Ser (likely pathogenic)), indicative of Hailey‐Hailey Disease. Sequence kernel association test analysis finds an increased burden of rare  ATP2C1  variants in the IC/BPS cases versus a control cohort ( p = 0.03, OR = 6.76), though does not survive Bonferroni correction. The data suggest that some individuals with IC/BPS may have unrecognized Mendelian syndromes. Comprehensive phenotyping and genotyping aid in understanding the range of diagnoses in the population‐based IC/BPS cohort. Conversely,   ATP2C1, ATP2A2,  and  SIX5  may be candidate genes for IC/BPS. Further evaluation with larger numbers is needed. Genetically screening individuals with IC/BPS may help diagnose and treat this painful disorder due to its heterogeneous nature. Abstract : Exome data for 109 individuals with interstitial cystitis/bladder pain syndrome is analyzed for Mendelian disorders. Two genes identified within the cohort, ATP2C1 and ATP2A2, are associated with dermatological phenotypes. Further evaluation with larger numbers is needed, though genetically screening individuals with IC/BPS may be useful in diagnosing and treating this painful disorder due to its heterogeneous nature.